Dumpty : the age of Trump in verse - Lithgow, John, 1945- (Chronicle Prism, an imprint of Chronicle Books, 2019)
Actor John Lithgow wields a satirical pen in this poetic diatribe chronicling the last few years in politics. He takes readers verse by verse through the history of Donald Trump's presidency, lampooning the likes of Betsy DeVos, Anthony Scaramucci, Scott Pruitt, Paul Manafort, Trump's doctors, and many others. Illustrated from cover to cover with Lithgow's own line drawings, the poems draw inspiration from A. A. Milne, Lewis Carroll, Edward Lear, Rodgers and Hammerstein, Mother Goose, and many more.